Prioritization of failure modes in manufacturing processes : a fuzzy logic-based approach - Singh, Jagdeep; Singh, Harwinder; Singh, Bhupinder (Emerald Publishing Limited, 2020)
Failure Mode and Effect Analysis (FMEA) are used to assess, investigate and predict the Risk Priority Number (RPN) of potential failures within the manufacturing industry. The authors use fuzzy logic as a tool to overcome the vagueness associated with traditional methods of assessing potential failures.